I.ii. Exercise book, containing a manuscript draft of sections of Kathleen Clarke's memoirs - Clarke, Kathleen, 1878-1972 (1946)
Clarke's notebook provides an account of her experiences between 2 May and July 1916, and describe raids on her home following the Easter Rising, her subsequent arrest, her husband Tom Clarke's execution, her last meeting with her brother Ned Daly prior to his execution, the death of her uncle John Daly (1 July) and other family matters. Also included is an account of the work of the National Aid and Volunteer Dependents Fund.
Annotations on the notebook's card cover read 'Book 2 May 1916'; annotations indicate the volume's contents were typed up on 24 June 1946.
The pages are not sequential in the book, but have been digitised to appear in sequence.
Keywords: Clarke, Thomas James, -- 1858-1916; Daly, Edward, -- 1891-1916; Ireland -- History -- Easter Rising, 1916